A new deepwater legskate, Sinobatis kotlyari n. sp. (Rajiformes, Anacanthobatidae) from the southeastern Indian Ocean on Broken Ridge - Stehmann, Matthias F. W.; Weigmann, Simon (Zootaxa, 2016)
Sinobatis kotlyari n. sp. is described, based on the nearly adult 331 mm TL holotype male from 1400 m depth in the southeastern Indian Ocean at Broken Ridge. The new species is assigned to Sinobatis due to mainly characters of its clasper and cranium fontanelle distinguishing it from congeners and other anacanthobatid skates with clasper features known. It further differs from its morphologically closest congener, S. borneensis, which is only known from the northwestern Pacific Ocean, e.g. in larger maturing size, longer snout and head, the absence of a snout filament and skin fold on tail, a longer caudal fin, and in colouration. The two congeners known from the eastern Indian Ocean, S. bulbicauda and S. cae-rulea, mature at much larger size, grow to larger maximum size and differ in numerous morphometric and meristic           characters, as well as in colouration. The type locality appears to be very remote as compared with other Indian Ocean legskates, which have primarily been found on continental and insular slopes.